Casca de arroz como precursora de carbono para obtenção de grafeno - Perez, Diego Marisco (2019)
This paper aims to study the synthesis and characterization of rice husk ash for the purpose of obtaining a high carbono content ash to produce graphene activated with potassium hydroxide. For that, different methods of burning applied at various temperatures with varied duration were used together with diferente analyzes by X-ray fluorescence (XRF), thermogravimetric analysis (TGA), Raman spectroscopy (RAMAN), CHN elemental analysis (CHN) and scanning electron microscopy (SEM). For the ash synthesis, a preliminary selection was first made on the rice husk, then washed with distilled water, and dried for 24 hours in a oven at 100 ºC. After these procedures, the rice husk was subjected to three different burning methods: muffle oven (FN), vacuum tube furnace (FC) and tubular furnace with continuous flow of nitrogen gas (FG), in order to determine the behavior of the rice husk during carbonization in different environments. For the three methods, all the samples were subjected to different temperatures (400, 500, 600 and 700 ° C), with different times (20, 40, 60 and 120 minutes) for each temperature. After the characterization of the ash, the sample of the tubular vacuum oven carbonized at 500 ° C for 60 minutes (FC 500-60) was chosen as best result because it contains an adequate percentage of amorphous carbon and presents a better cost / benefit of production, if compared to other methods. For the graphene production, 1 g of the selected sample ash was activated with 4 g potassium hydroxide (KOH) at temperatures of 700, 750, 800 and 850 ° C for 2 hours in order to determine the best activation temperature. However, graphene was only obtained at the temperature of 850 ° C (GFN 850), where the material presented defined peaks in the bands D, G and 2D. These band indicate the presence of ordered carbon, but with defects in the structure; the production of graphene was estimate to be 4 to 8 layers of graphene, in which the nanomaterial presented morphology similar to corrugated paper. These results show that it is possible to obtain graphene from alternative materials using low cost technologies.